PENGETAHUAN DAN TINDAKAN KADER TB DALAM UPAYA PENGENDALIAN PENYAKIT TB PARU DI KABUPATEN KEPULAUAN MERANTI - Pebryanty, Putri; Restuastuti, Tuti; ", Zahtamal (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTTuberculosis is contagious disease that caused by Mycobacterium tuberculosis. Public health office of Riau Province stated that Case Detection Rate (CDR) of pulmonary TB in 2013 was 35,7% of 5.648.523 people. The case finding of TB with positive acid-fast bacilli in 2014 in Meranti Islands Regency was 16,95%. Meranti Islands Regency is one of regency having trained people to be TB cadre. This research aimed to know the knowledge and action of cadre in managing pulmonary TB in Meranti Islands Regency. This research was conducted on February 2017 in Alai Public Health Centre, West Tebing Tinggi District, Meranti Islands Regency. This research used qualitative descriptive design. Data was taken by deep interview with cadre that fulfilled critetria, then triangulation was done with supporter informants. This research showed that the knowledge of TB cadre to TB was good enough especially about the definition, symptomps, and risk people having TB. While they still had lack of knowledge about the causing agent and transmission of TB. The action of TB cadtre in Alai Public Health Centre was not ideal especially in referring TB suspect. While case finding of TB, counseling, supervision for administering medication, and motivating had been good.Keyword: Knowledge, action, management of TB, TB cadre